The accountant [videorecording (Blu-Ray)] - Dubuque, Bill; Affleck, Ben, 1972-; Kendrick, Anna; Simmons, J. K.; Bernthal, Jon; Tambor, Jeffrey, 1944-; Lithgow, John, 1945-; Isham, Mark; McGarvey, Seamus, 1967- (Warner Bros. Entertainment, Inc., 2017)
Christian Wolff is a math savant who works as a freelance accountant for some of the world's most dangerous criminal organizations. With the Treasury Department's Crime Enforcement Division starting to close in, he takes on a legitimate client, a robotics company where an accounting clerk has discovered a discrepency involving millions of dollars. But as Christian uncooks the books and gets closer to the truth, the body count starts to rise.